Marine litter: trends and impacts in marine fauna - Sá, Sara Maria Fardilha Alves de (2025)
Marine litter, defined as any solid, human-made material discarded in marine environments, originates from both land- and ocean-based sources. Plastics are the most persistent and prevalent component of marine litter, due to their durability, low cost, and widespread use across industries. Microplastics, which can either be intentionally manufactured or result from the breakdown of larger plastic items, are now pervasive contaminants, transported by ocean currents and present across all marine habitats. Marine litter poses significant ecological risks, impacting marine life through ingestion, entanglement, habitat destruction, and increased invasive species dispersal. Microplastics are particularly harmful due to their high bioavailability across trophic levels and their ability to adsorb and transport toxins that bioaccumulate in marine organisms, potentially leading to physiological harm, including endocrine disruption and organ toxicity and dammage. Marine mammals, as top predators and pollution indicators, serve as key sentinels for monitoring the impacts of marine plastic pollution on ecosystem health. Cetaceans are at increased risk in litter-aggregated oceanic zones. In Portuguese waters, with high cetacean diversity (28 species), marine litter poses risks through ingestion and entanglement, leading to harmful physiological effects, impaired migration, and even death. In this study, a particular group of floating litter categories (DDFC-Dangerous Debris for Cetaceans) that may pose the greatest threat to cetaceans was evaluated through a shipboard survey covering a 252,833 km² area off continental Portugal. Plastic was the dominant litter type (56.53%), followed by derelict fishing gear (10.14%), which poses particular risks to cetaceans. High accumulation of litter near the Gorringe Bank highlighted the important impact of discarded fishing gear, particularly on cetaceans that may feed in these highly productive areas. While DDFC hotspots and cetacean distributions mostly did not overlap, certain areas showed a moderate risk of interactions. Another survey of floating macrolitter in a coastal NATURA 2000 area (PTCON0063 Maceda-Praia da Vieira), Portugal, revealed high densities of litter (4.856 items/km²), primarily plastics, in comparison to offshore waters. A hotspot for floating macrolitter was identified between Porto and Aveiro, linked to the main urban centres and river discharge. Plastic packages and fishing items were the most common macrolitter items, indicating sources related to consumer waste and local fisheries. In the same coastal NATURA 2000 area, samples from a net tow survey revealed that microplastics were mainly represented by fibres (2018: 92.66%; 2019: 80.91%), likely originating from textile industries and wastewater treatment plants, which struggle to retain synthetic fibres. In the surveyed area, blue fibres were predominant (they were later found to be common in cetacean digestive tracts) as well as white and transparent microplastic fragments, which suggest in-situ breakdown of larger plastics. These results underscore the influence of local pollution sources. The analysis of marine litter ingestion in cetaceans stranded along the Portuguese coast (Delphinus delphis, Phocoena phocoena, and Stenella coeruleoalba) revealed a high microplastic ingestion among individuals (F.O.%=92.11%), with microfibers being the most common type (76.77%), reflecting their prevalence in the Portuguese coastal environment. Striped dolphins showed higher ingestion of plastic fragments (F.O.%=83.33%), likely due to their offshore habitats where litter accumulates. The shapes of ingested fragments suggest they originated from the breakdown of larger plastics. Findings support the "secondary ingestion" hypothesis, as the characteristics of microplastics described in fish (common prey for the evaluated cetacean species) matched those found in the analysed cetaceans. While the sample size was limited, higher microplastic ingestion in harbour porpoises may stem from their demersal feeding habits. Although immediate toxic effects were not evident, the potential of microplastics as pollutant vectors raises concerns, especially for at-risk populations like the Iberian harbour porpoise, warranting further research on pollutant bioaccumulation in cetaceans. Finally, the evaluation of macrolitter ingestion in deep-diving cetaceans revealed a high frequency of occurrence of ingested marine litter (45.61%). This ingestion resulted in significant lethal (30.77%) and sublethal (53.85%) effects, highlighting its role as a major contributor to mortality in species that forage on or near the seafloor, such as Cuvier’s beaked whales, sperm whales, and pygmy sperm whales along the Atlantic Iberian Coast. Lethal ingestion was specifically noted in these species, with reported rates of 41.67%, 40.00%, and 20.00%, respectively. The prevalence of litter ingestion is linked to their benthic feeding behaviour, as these species often consume cephalopods through suction and may inadvertently ingest marine litter. This study supports the proposal of sperm whales as a global indicator species for macrolitter in the deep ocean. Challenges in accurately assessing the impact of marine litter on deep diving cetaceans include the rarity of these species and the underreporting of strandings, emphasising the need of improved sampling methods through marine animal strandings networks to gather more comprehensive data on their macrolitter ingestion. Long-term studies with broader temporal and spatial scales are essential to understand the risk of marine litter to cetacean populations and the factors affecting their distribution. Continuous monitoring of stranded cetaceans is necessary to evaluate population-level impacts and standardized protocols for microplastic analysis (in water and in biota) should be established to enable accurate assessments and comparisons across different regions.